Insegnamento del beato Giovanni Duns Scoto sulla menzogna sullo sfondo della teoria scotiana dell’atto morale umano - Krzysztof Niewiadomski (Warszawskie Studia Teologiczne)
The paper undertakes a study on the issue of a lie in morality, in the theory of Bl. John Duns Scotus. The Franciscan theologian shows iniquity of this act on the basis of a bad intention. The object alone isn’t sufficient for a final moral qualification. This teaching is consistent with Duns Scotus' theory of the moral act and it confirms it. It harmonizes with his metaphysics and epistemology.